Study of the machinability of compacted graphite iron for drilling process - Mocellin,F. (2004)
CGI - Compacted Graphite Iron - has reached an important status for automotive industry, mainly in the last ten years. The material has been used for manufacturing parts as brake discs, exhaust manifolds, engine heads and diesel engine blocks. The superior strength characteristics of CGI, as compared to gray iron, allows the manufacturing of engines for higher pressure operating combustion chambers, therefore more efficient and with lower emissions levels. Also thinner walls are possible, generating lighter engines. However there are some technical challenges to overcome, mainly related to the machining process of the parts. This research intends to study the machinability of CGI, in order to develop a new alloy with improved characteristics of machinability, so the production costs for CGI automotive parts can be reduced. The study uses a reference material, gray iron FC-250, widely used for engine blocks manufacturing. The machinability of the referred material is compared to five different CGI alloys by means of drilling experiments. The considered machinability criteria are the tool wear and the cutting forces. The experiments led to the development of a CGI-450 with machinability 83% (relative to FC-250), therefore with excellent potential qualities for engine block and other auto parts manufacturing.